Anchoring Growth : The Importance of Productivity-Enhancing Reforms in Emerging Market and Developing Economies - Dabla-Norris, Era (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
Fostering and sustaining robust economic growth is an imperative across advanced, emerging, and low-income countries alike. Countries will need to focus on supply-side reforms to raise their potential output and anchor medium-term growth prospects. This SDN will emphasize the role of structural reforms and supportive policy and institutional frameworks for boosting productivity-a key engine of economic growth-in the wake of the crisis. By examining a broad spectrum of reforms that eliminate impediments to growth, the paper will seek to highlight a differentiated policy agenda across countries.